Terrestrial Mollusks (Gastropoda) of the Slovechansko-Ovrutsky Ridge (Zhytomyr Region, Northern Ukraine) - Balashov, I. (Вестник зоологии, 2012)
Thirty-five species of terrestrial mollusks were found in the Slovechansko-Ovrutsky ridge. Findings of Clausilia cruciata, Ruthenica filograna and Monachoides vicinus are especially interesting. Reproductive system of Morlina glabra is described. Problems of the conservation of terrestrial mollusks in the region are discussed. На территории Словечанско-Овручского кряжа зарегистрированы 35 видов наземных моллюсков. Особо интересны находки таких видов как Clausilia cruciata, Ruthenica filograna и Monachoides vicinus. Приведено описание половой системы Morlina glabra. Обсуждаются проблемы охраны наземных моллюсков в регионе.